Influence of joint angular velocity on electrically evoked concentric force potentiation induced by stretch-shortening cycle in young adults - Fukutani, Atsuki (Springerplus, 2015)
BACKGROUND: During a stretch- shortening cycle (SSC), muscle force attained during concentric contractions (shortening phase) is potentiated by the preceding eccentric contractions (lengthening phase). The purpose of this study was to examine the influence of joint angular velocity on force potentiation induced by SSC (SSC effect). FINDINGS: Twelve healthy men (age, 24.2 ± 3.2 years; height, 1.73 ± 0.05 m; body mass, 68.1 ± 11.0 kg) participated in this study. Ankle joint angle was passively moved by a dynamometer, with range of motion from dorsiflexion (DF) 15° to plantarflexion (PF) 15°. Muscle contractions were evoked by tetanic electrical stimulation. Joint angular velocity of concentric contraction was set at 30°/s and 150°/s. Magnitude of SSC effect was calculated as the ratio of joint torque obtained by concentric contraction with preliminary eccentric contraction trial relative to that obtained by concentric contraction without preliminary eccentric contraction trial. As a result, magnitude of SSC effect calculated at three joint angles was significantly larger in the 150°/s condition than in the 30°/s condition (p < 0.05). CONCLUSIONS: These results indicate that the magnitude of SSC effect is affected by joint angular velocity, which is larger when joint angular velocity is larger. This phenomenon would be caused by insufficient duration to increase activation level in the large joint angular velocity condition. When the duration to increase activation level is insufficient due to short contraction duration, preactivation (one of the factors of SSC effect) leads to a significant increase in joint torque.